SOSIALISASI PREMARITAL CARE DALAM PENCEGAHAN STUNTING DI WILAYAH KERJA PUSKESMAS LUBUK BUAYA - Marisa Lia Anggraini; Silvie Permata Sari; Putri Minas Sari (Khidmah, 2022)
Stunting is one of the nutritional problems that can significantly hinder human development. Children are defined as stuned if their height for age is less than negative two standard deviations below the median Child Gworth Standarts (WHO, 2013). The incidence of stunting is very high, in developing countries. Globally, the incidence of stunting is 162 million children under the age of 5 years (WHO, 2013). In Indonesia, the prevalence of stunting is around 37% (Tumilowicz A, 2018). The prevalence of stunting is higher in children aged 2 years and decreases with increasing age (Sefors P, 2018). The direct impact of stunting is short adult stature, less body mass, reduced intellectual function, reduced income and lower birth weight of babies born to women who experienced stunting as children, as well as an increased risk of death in infants born to stunting moyhers (Dewey KG, 2011). In addition, the decline in cognitive function in stuned children will have a long-term impact on the lack of education received and the tendency to live in the poverty line (Visser J, 2016).